1975
DOI: 10.1139/v75-161
|View full text |Cite
|
Sign up to set email alerts
|

Complexes of 2-Mercaptobenzothiazole with Cu(II), Ni(II), Co(II), Cd(II), Zn(II), Pb(II), Ag(I), and Tl(I)

Abstract: The complexes of 2-mercaptobenzothiazole with Cu(II), Ni(II), Co(II), Cd(II), Zn(II), Pb(II), Tl(I), and Ag(I) have been synthesized. Their structures have been assigned on the basis of analytical, spectral (i.r. and visible), and magnetic data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…The heterocyclic system of the most potent antifungal agent is indeed anchored nearly perpendicular to the heme group of CA‐CYP51, by means of a coordination bond involving the iron atom and the sulfur in its thione tautomeric form, as it might be perceived from the docking 2f depicted in Figure . As a figure of merit, a similar type of coordination has been proved by studies carried out on the basis of analytical, spectral (IR and VIS), and magnetic data . At the same time, the chlorine atom at 6‐position of the benzothiazole moiety reinforces the binding with favorable Van der Waals interactions engaged with the residues at the boundary of a reduced accessible surface of the active site lodge, shaped and delimited by residues, namely, Tyr118, Leu121, Phe228, His310, Met508, and Val509.…”
Section: Resultssupporting
confidence: 67%
“…The heterocyclic system of the most potent antifungal agent is indeed anchored nearly perpendicular to the heme group of CA‐CYP51, by means of a coordination bond involving the iron atom and the sulfur in its thione tautomeric form, as it might be perceived from the docking 2f depicted in Figure . As a figure of merit, a similar type of coordination has been proved by studies carried out on the basis of analytical, spectral (IR and VIS), and magnetic data . At the same time, the chlorine atom at 6‐position of the benzothiazole moiety reinforces the binding with favorable Van der Waals interactions engaged with the residues at the boundary of a reduced accessible surface of the active site lodge, shaped and delimited by residues, namely, Tyr118, Leu121, Phe228, His310, Met508, and Val509.…”
Section: Resultssupporting
confidence: 67%
“…The value of Racah parameter B decreases from 971 cm -1 in free Co(II) ion to 780-748 cm -1 in complexes. These crystal field parameter values undoubtedly indicate the octahedral symmetry of Co(II) complexes [45][46][47]. The magnetic moment of Ni(II) complexes has been found 3.0-3.1 B.M., which is slightly higher than two unpaired electrons of d 8 -system which may be due to spin-orbit coupling effect [48].…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports dealing with complexes of copper ions with phosphine and neutral heterocyclic thiones revealed that in the majority of these compounds, heterocyclic thiones prefer a monodentate binding mode, coordinating exclusively through exocyclic sulfur atom. [ 39–43 ] Due to soft nature of sulfur atom in heterocyclic thiones, we speculated that copper–phosphine complexes with thiolates would provide interesting mixed‐ligand coordination complexes, suitable for certain catalytic reactions. Structural characterization of a catalytic system is an important step in aiming at mechanistic understanding of a catalytic process.…”
Section: Introductionmentioning
confidence: 99%